SMPD1 mutations, activity, and α‐synuclein accumulation in Parkinson's disease. Issue 4 (20th February 2019) - Alcalay, Roy N.; Mallett, Victoria; Vanderperre, Benoît; Tavassoly, Omid; Dauvilliers, Yves; Wu, Richard Y.J.; Ruskey, Jennifer A.; Leblond, Claire S.; Ambalavanan, Amirthagowri; Laurent, Sandra B.; Spiegelman, Dan; Dionne‐Laporte, Alexandre; et al.
Abstract: Background: SMPD1 (acid‐sphingomyelinase) variants have been associated with Parkinson's disease in recent studies. The objective of this study was to further investigate the role of SMPD1 mutations in PD. Methods: SMPD1 was sequenced in 3 cohorts (Israel Ashkenazi Jewish cohort, Montreal/Montpellier, and New York), including 1592 PD patients and 975 controls. Additional data were available for 10, 709 Ashkenazi Jewish controls. Acid‐sphingomyelinase activity was measured by a mass spectrometry‐based assay in the New York cohort. α‐Synuclein levels were measured in vitro following CRISPR/Cas9‐mediated knockout and siRNA knockdown of SMPD1 in HeLa and BE(2)‐M17 cells. Lysosomal localization of acid‐sphingomyelinase with different mutations was studied, and in silico analysis of their effect on acid‐sphingomyelinase structure was performed. Results: SMPD1 mutations were associated with PD in the Ashkenazi Jewish cohort, as 1.4% of PD patients carried the p.L302P or p.fsP330 mutation, compared with 0.37% in 10, 709 Ashkenazi Jewish controls (OR, 3.7; 95%CI, 1.6‐8.2; P = 0.0025). In the Montreal/Montpellier cohort, the p.A487V variant was nominally associated with PD (1.5% versus 0.14%; P = 0.0065, not significant after correction for multiple comparisons). Among PD patients, reduced acid‐sphingomyelinase activity was associated with a 3.5‐ to 5.8‐year earlier onset of PD in the lowest quartile versus the highest quartile of acid‐sphingomyelinase activity ( P = 0.01‐0.001). We further demonstrated that SMPD1 knockout and knockdown resulted in increased α‐synuclein levels in HeLa and BE(2)‐M17 dopaminergic cells and that the p.L302P and p.fsP330 mutations impair the traffic of acid‐sphingomyelinase to the lysosome. Conclusions: Our results support an association between SMPD1 variants, acid‐sphingomyelinase activity, and PD. Furthermore, they suggest that reduced acid‐sphingomyelinase activity may lead to α‐synuclein accumulation. © 2019 International Parkinson and Movement Disorder Society